Flutter Analysis on the Wing of Typical 4.5th Generation Fighter Aircraft - Ahmad Hasan Fauzi (ROTASI, 2023)
Flutter is a phenomenon of dynamic instability caused by aerodynamic force, inertial force, and structural elasticity. It is recognized by catastrophic oscillation of the structure at a certain flow speed. In aircraft design, flutter analysis must be conducted to ensure that the aircraft does not undergo flutter in its operational region. This work focuses on flutter analysis of the wing of a 4.5th generation fighter aircraft, using the MSC.FLDS/PATRAN/NASTRAN software. The process involves several procedures, including structure modeling, structural dynamics analysis, aerodynamic load modeling, and flutter analysis. The structure is modeled using the finite element method, while the doublet lattice method is used for aerodynamic load modeling in the subsonic regime and ZONE 51 in the supersonic regime. The p-k method is used to solve the flutter analysis. After conducting flutter analysis in the basic configuration and condition, a parametric study is performed to understand how some parameters affect the change in flutter characteristics. The results of the parametric study show that the speed and characteristics of flutter change with changes in flight conditions (altitude and Mach number) and mass configuration (position of the missile in the spanwise direction). Flight conditions change the aerodynamic load in the system, while missile position and structure thickness change the inertia and stiffness of the system. Changes in these parameters - aerodynamic, inertia, and stiffness - affect the flutter speed and characteristics.